Multilevel analysis of evolution of team process and their relation to performance in semi-professional soccer - Leo, F. M.; López-Gajardo, M. A.; Pulido, J. J.; González-Ponce, I. (International Journal of Sports Science & Coaching, 2022)
The aim of the study was to examine the evolution of players' perception of group variables (leadership, motivational climate, cohesion, and collective efficacy) and to determine whether the intercept and growth trajectory differed as a function of whether expectations have or have not been met in a sample of semi-professional Spanish football players. The results show that the levels of the variables (except for autocratic leadership and coach-created ego climate) decrease over the season. Furthermore, the mean scores of the fully meets expectations group were significantly higher in positive leader characteristics, coach-created task climate, cohesion and collective efficacy. Also, rates of decline were significantly greater in the does not meet expectations group. The results indicate the importance of establishing reachable expectations by coaches and players because to achieve or to miss the expected goals can affect psychological group dynamics.